Workload and Its Influence on Employee Performance - Lisna, Yuke Permata (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2024)
This study aims to analyze the effect of workload on employee performance in the service and hospitality sector in Padang City. The research involved 200 employees selected through purposive sampling. The workload variable was measured through physical, mental, and time aspects, while employee performance was assessed using indicators of quantity, quality, timeliness, and teamwork. Data were analyzed using simple linear regression with the assistance of SPSS. The findings indicate that workload is predominantly in the high category (46%), while employee performance is mostly in the good (44%) and very good (33%) categories. Regression results show that workload has a significant effect on employee performance, with a significance value of 0.000 < 0.05 and a negative regression coefficient (-0.421). This indicates that the higher the perceived workload, the lower the employee performance. Nevertheless, most employees are still able to maintain good performance through teamwork and work experience. This study highlights the importance of workload management through proportional task distribution, effective work scheduling, and managerial support to sustain and enhance employee performance in the service and hospitality sector